Effect of NaOH Concentration and Immersion of Ice Water on Physical and Mechanical Characteristics of Candlenut Seeds (Aleurites moluccana L Willd) - Muchammad Zakaria; La Choviya Hawa; Gunomo Djoyowasito (The Indonesian Green Technology Journal, 2019)
The breakdown of candlenut seeds from the shell is very important to note due to the increasing consumption needs of candlenut seeds in the market has not been able to be balanced with the quality of the breakdown of good candlenut seeds. The purposed of this research was to identified the physical and mechanical properties of candlenut, analyzed the strength of the candlenut seeds that was in the treatment, analyzed the mass of the candlenut seeds which stick to the shell, analyzed the level of integrity of the candlenut seeds. This research was conducted using factorial randomized block design (RAKF) method with 2 factors. The first factor was the variation of NaOH concentration, while the second factor was the time of immersion ice water. Pressed load testing of candlenut shell used brazillian test, from this research was obtained the result of press load candlenut seeds with variations of NaOH immersion and the immersion time of ice water 10 and 45 minutes on average were 31.28 N and 22.30 N, while the load control was 44.692 N. Mass the seed core that was still sticky to the shell with the treatment given was an average value of 0.114 gr (3.8%) and 0.033 gr (1.2%), while the control is 1,753 gr (63%). The whole candlenut seeds core results with the given treatment were 7 grains (31.8%) and 15 grains (64%), whereas the control did not get the whole candlenut seeds core. The results of research is shows that the parameters of the increase in NaOH concentration does not have a significant effects but when compare with the control of NaOH it is very significant for the breakdown of candlenut, while the time parameters have a very significant effects.Keywords: NaOH, Ice water immersion, The process of breaking candlenut,